2021
DOI: 10.1007/s40257-021-00591-x
|View full text |Cite|
|
Sign up to set email alerts
|

The PROVe Study: US Real-World Experience with Chlormethine/Mechlorethamine Gel in Combination with Other Therapies for Patients with Mycosis Fungoides Cutaneous T-Cell Lymphoma

Abstract: Background Chlormethine/mechlorethamine gel is a skin-directed therapy for patients with mycosis fungoides cutaneous T-cell lymphoma. Currently, real-world data on chlormethine gel are lacking. Objective Our objective was to analyze the effect of chlormethine gel in combination with other therapies on efficacy, safety, and health-related quality of life in a real-world setting. Methods This prospective, observational study enrolled adult patients actively using chlormethine gel. Patients were monitored for up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(84 citation statements)
references
References 17 publications
4
77
3
Order By: Relevance
“…Efforts are ongoing to gain a more in-depth understanding of the utility of chlormethine gel in patients with MF and the nature of the emergent skin reactions. The PROVe trial found that chlormethine gel is an effective treatment across all disease stages [ 45 ]. No chlormethine gel-related serious AEs occurred in the study, and the reported emergent skin-related AEs were manageable and less prevalent than in the pivotal clinical trial [ 15 ], possibly because of frequent dose adjustments and the co-administration of corticosteroids, which reflect the real-world experience reported herein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts are ongoing to gain a more in-depth understanding of the utility of chlormethine gel in patients with MF and the nature of the emergent skin reactions. The PROVe trial found that chlormethine gel is an effective treatment across all disease stages [ 45 ]. No chlormethine gel-related serious AEs occurred in the study, and the reported emergent skin-related AEs were manageable and less prevalent than in the pivotal clinical trial [ 15 ], possibly because of frequent dose adjustments and the co-administration of corticosteroids, which reflect the real-world experience reported herein.…”
Section: Discussionmentioning
confidence: 99%
“…A peak response occurred at 18 months for patients with stage IA and IB disease in the chlormethine plus other treatment group (67%). Overall, 28% of patients experienced a treatment-related AE; the most common skin-related AEs deemed to be therapy related were dermatitis (12%), pruritus (7%), skin irritation (7%), and erythema (4%) [ 45 ].…”
Section: Chlormethine In Mf Management: a Review Of The Literaturementioning
confidence: 99%
“…The PROVe study (a PROspective, observational study assessing outcomes, adverse events [AEs], treatment patterns, and QOL in patients diagnosed with MF and treated with Valchlor and other therapies) examined the use of CL gel in clinical practices across the USA over a 2-year period [ 38 , 57 ]. In total, 298 patients were treated with CL gel.…”
Section: Efficacy Of CL Gel Treatmentmentioning
confidence: 99%
“…(mechlorethamine [USAN]) 0.02% gel. 117 In a phase 2 trial, patients with stage IA-IIA MF were treated with 0.02% gel daily for up to 12 months. A response was observed in 58.5% of patients, with 13.8% achieving a complete response.…”
Section: Topical Therapiesmentioning
confidence: 99%
“…In an uncontrolled prospective study, topical clobetasol propionate was used in 85% of patients with stage 1 A/B disease, had an overall response rate of 94%, and is associated with minimal to no toxicity 115,116. An alternative topical medication is chlormethine (INN) (mechlorethamine [USAN]) 0.02% gel 117. In a phase 2 trial, patients with stage IA-IIA MF were treated with 0.02% gel daily for up to 12 months.…”
mentioning
confidence: 99%